Asymmetric synthesis of (4R,5R)-cytoxazone and (4R,5S)-epi-cytoxazone. - Davies, S; Hughes, D; Nicholson, R; Smith, A; Wright, A (2004)
(4R,5R)-Cytoxazone has been prepared in four steps and in 61% overall yield and >98% ee. Conjugate addition of lithium (R)-N-benzyl-N-[small alpha]-methylbenzylamide to tert-butyl (E)-3-(p-methoxyphenyl)prop-2-enoate and subsequent in situ diastereoselective enolate oxidation with (+)-(camphorsulfonyl)oxaziridine gave tert-butyl (2R,3R,[small alpha]R)-2-hydroxy-3-(p-methoxyphenyl)-3-(N-benzyl-N-[small alpha]-methylbenzylamino)propanoate in >98% de. Subsequent N-benzyl deprotection to the primary [small beta]-amino ester via hydrogenolysis, oxazolidinone formation with C(2)-retention by treatment with diphosgene and chemoselective ester reduction furnishes (4R,5R)-cytoxazone. The synthesis of the C(5)-epimer, (4R,5S)-epi-cytoxazone in 44% overall yield, has also been completed via a protocol involving N-Boc protection of the primary [small beta]-amino ester, utilization of the N-Boc group to facilitate simultaneous C(2)-inversion and oxazolidinone formation, and subsequent reduction.